Perspektif Pendirian Bank Pertanian di Indonesia (Forum Penelitian Agro Ekonomi, 2016)
EnglishThe role of agricultural sector is very important to enhance the national economic development although its development is not fully supported by sufficient capital. The existing formal financial institutions tend to prioritize non-agricultural services which have high profit but low risk. In this context, efforts to establish agricultural bank institution that especially support agricultural activity services are highly recommended. This paper aimed at a review of the urgency, possibility, potential, and constraints of agricultural bank establishment in Indonesia. The result showed that conceptually and empirically, agricultural bank institution has a promising prospective in Indonesia. There are many options in respect to agricultural bank establishment in Indonesia, such as (1) Credit-agricole ÃƒÆ’Ã‚Â¢ÃƒÂ¢Ã¢â‚¬Å¡Ã‚Â¬Ãƒâ€¦Ã¢â‚¬Å“France modelÃƒÆ’Ã‚Â¢ÃƒÂ¢Ã¢â‚¬Å¡Ã‚Â¬Ãƒâ€šÃ‚Â, (2)ÃƒÆ’Ã¢â‚¬Å¡Ãƒâ€šÃ‚Â  ÃƒÆ’Ã‚Â¢ÃƒÂ¢Ã¢â‚¬Å¡Ã‚Â¬Ãƒâ€¦Ã¢â‚¬Å“Bank BukopinÃƒÆ’Ã‚Â¢ÃƒÂ¢Ã¢â‚¬Å¡Ã‚Â¬Ãƒâ€šÃ‚ÂÃƒÆ’Ã¢â‚¬Å¡Ãƒâ€šÃ‚Â  model, (3) foreign direct investment model, (4) upgrading of ÃƒÆ’Ã‚Â¢ÃƒÂ¢Ã¢â‚¬Å¡Ã‚Â¬Ãƒâ€¦Ã¢â‚¬Å“BUMN BankÃƒÆ’Ã‚Â¢ÃƒÂ¢Ã¢â‚¬Å¡Ã‚Â¬Ãƒâ€šÃ‚Â to ÃƒÆ’Ã‚Â¢ÃƒÂ¢Ã¢â‚¬Å¡Ã‚Â¬Ãƒâ€¦Ã¢â‚¬Å“Agricultrual BankÃƒÆ’Ã‚Â¢ÃƒÂ¢Ã¢â‚¬Å¡Ã‚Â¬Ãƒâ€šÃ‚Â model, and (5) utilizing the financial institution that locally available and accessible by the people. For efficient and effective of the services, the agricultural bank should be designed based on agricultural characteristics and typical actors of agricultural business.IndonesianPeran sektor pertanian yang sangat strategis dalam perekonomian nasional belum diimbangi dengan dukungan penyediaan modal yang memadai.ÃƒÆ’Ã¢â‚¬Å¡Ãƒâ€šÃ‚Â  Lembaga perbankan formal yang ada saat ini cenderung bias dan lebih mengutamakan pembiayaan non pertanian. Dengan memperhatikan fenomena tersebut, perlu upaya pembentukan lembaga keuangan yang khusus bergerak dalam pembiayaan sektor pertanian. Salah satu wacana tentang bentuk lembaga keuangan tersebut adalah dengan mendirikan Bank Pertanian. Tulisan ini bertujuan melakukan tinjauan mengenai urgensi, potensi dan kendala pembentukan bank pertanian di Indonesia. Hasil kajian menunjukkan bahwa secara konseptual maupun empirik, Bank Pertanian sangat prospektif untuk diwujudkan di Indonesia. Ada beberapa format Bank Pertanian yang dapat menjadi pilihan di antaranya (i) pola pendirian credit-agricole Perancis, (ii) pola pendirian bank Bukopin, (iii) investasi langsung modal asing (iv) mendorong bank BUMN menjadi bank pertanian, serta (v) memanfaatkan lembaga keuangan yang tumbuh dan berkembang di tingkat lokal. Agar Bank Pertanian dapat melayani nasabah secara efektif dan efisien, maka bank tersebut harus didesain sesuai dengan kekhasan karakteristik sektor pertanian dan pelaku usaha pertanian.